Diabetic retinopathy prevalence in the Russian Federation according to all-Russia statistics - V. V. Neroev; O. V. Zaitseva; L. A. Mikhailova (Российский офтальмологический журнал, 2023)
In Russia, a complex approach to diabetes mellitus and diabetic retinopathy (DR) treatment is adopted, yet certain issues remain in the system of medical care for DR patients. The statistical data are important to assess the availability and quality of medical care in each region of the Russian Federation, to plan resource distribution, and determine the volume of medicinal and technical support. The article presents an analysis of the territorial differences of DR prevalence and of dispensary follow-up of DR patients. In order to eliminate certain territorial defects in the organization of medical care for such patients, an improvement of outpatient medical aid organization and a more effective interaction between ophthalmological and endocrinal health services is required.